Impact of Aging in Microglia-Mediated D-Serine Balance in the Cns - Eugenin-Leon, J (Hindawi Limited, 2018)
A mild chronic inflammatory state, like that observed in aged individuals, affects microglial function, inducing a dysfunctional phenotype that potentiates neuroinflammation and cytotoxicity instead of neuroprotection in response to additional challenges. Given that inflammatory activation of microglia promotes increased release of D-serine, we postulate that age-dependent inflammatory brain environment leads to microglia-mediated changes on the D-serine-regulated glutamatergic transmission. Furthermore, D-serine dysregulation, in addition to affecting synaptogenesis and synaptic plasticity, appears also to potentiate NMDAR-dependent excitotoxicity, promoting neurodegeneration and cognitive impairment. D-serine dysregulation promoted by microglia could have a role in age-related cognitive impairment and in the induction and progression of neurodegenerative processes like Alzheimer s disease. © 2018 Sebastián Beltrán-Castillo et al. This is an open access article distributed under the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.